Pengembalian Aset (Aset Recovery) Pelaku Tindak Pidana Korupsi - Gomgom TP Siregar (UNES Law Review, 2023)
Corruption is a special crime with distinct characteristics that differentiate it from general crimes, including non-compliance with formal criminal or procedural laws. In Indonesia, corruption still reigns as the most prevalent form of criminal activity. This study is a descriptive analytical research, focused on the presentation of phenomena and circumstances related to the financial returns and/or state assets affected by acts of corruption. The research excludes subjective evaluations unless marked as such, and emphasizes clear, concise sentences and logical structure. Technical term abbreviations are defined upon first use. The paper adheres to conventional academic sections and formatting, including clear and factual titles. The language is objective, neutral and grammatically correct. The text maintains a formal register, avoiding contractions, colloquialisms, and unnecessary jargon. Causal connections between statements are made clear, while biased language is avoided. Precise, subject-specific vocabulary is employed when applicable. In addition, the document adheres to language-specific spellings, grammar, and style. Law Number 20 from 2001 addresses corruption as a criminal offence. Article 18 discusses additional crimes to recover state finances. Law Number 7 from 2006 ratifies the United Nations Convention Against Corruption of 2003 which details how assets seized from corrupt criminals can occur through both criminal and civil channels. Law Number 1 of 2006, governing mutual assistance in criminal matters, serves as the basis for the Indonesian government's provision of as well as requests for mutual assistance. It also provides guidelines for entering agreements in criminal matters with foreign countries. Several channels/instruments are available for reclaiming assets from corruption crimes, including criminal, civil, and administrative means.